Analisis Yuridis Penerapan Justice Collaborator Dalam Tindak Pidana Korupsi (Studi Putusan Mahkamah Agung Nomor 430 K/Pid.Sus/2018) - Novitha Sitohang; Firman Wijaya (Fakultas Hukum Universitas Tarumanagara, 2021)
Justice Collaborator can be said to be an extraordinary legal effort and has a very meaningful role in uncovering the problem of corruption, even though its implementation often arises problems. The problem in this thesis is how is the implementation of Justice Collaborator in Corruption Crime (Study of Supreme Court Decision Number 430K / Pid.Sus / 2018). The research method in the preparation of this thesis is a normative juridical research method, namely research is carried out by first examining the law library materials related to the case and then being viewed objectively through the provisions of the applicable legislation. This research has a descriptive character, namely describing and analyzing the cases presented which aim to describe concretely about the juridical study of the application of Justice Collaborator in criminal acts of corruption in Indonesia. In the research conducted by the author, it can be concluded that in SEMA Number 4 of 2011, a juice collaborator is given to one of the perpetrators of a certain crime, admits that he was committed, not the main actor in the crime itself, and can provide information as a witness in the judicial process. Certain criminal acts referred to in this SEMA are corruption, terrorism, narcotics, money laundering, human trafficking, and other organized crimes. Thus, this criminal act can cause serious problems and threats to the stability and security of society, however, the priority that is centered in this SEMA is the Crime of Corruption.